Analyzing P2P Landing Usage Intention (Case Study of Four P2P Lending Applications in Indonesia) - Dzakwan Nafis Hestopo; Mahir Pradana (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
This research was conducted to find out the interest in using pay later peer to peer lending features as an online payment medium using an innovation diffusion model that there are several characteristics including relative advantages, compatibility, complexity, trialability, and observability. Primary data collection was done using purposive sampling techniques as many as 100 respondents who are users of pay later features. The dissemination of questionnaires was done online through social media. The results of this study prove that variables of relative advantages, compatibility, complexity, trialability, and observability simultaneously have a significant influence on individual interests in adopting P2P lending services.